Physical activity in patients after bariatric surgery - a literature review - Śliwińska, Martyna; Podraza, Anna; Wirkijowska, Małgorzata; Wirkijowski, Jakub; Wójtowicz, Katarzyna; Walczak, Agata; Gajek-Flanczewska, Wiktoria; Flanczewski, Sebastian; Woźniak, Paulina; Wietrzykowska, Ewa; Sobolewska, Dominika; Michalczyk-Fraszka, Katarzyna (Quality in Sport, 2025)
Introduction: Obesity is a growing global health concern, leading to severe comorbidities such as cardiovascular disease, diabetes, and depression. Bariatric surgery is an effective treatment for severe obesity, providing significant weight loss and health improvements. However, physical activity (PA) plays a critical role in enhancing these outcomes, including sustained weight loss, improved fitness, and better mental health. Materials and methods: The authors searched PubMed, UpToDate, Google Scholar, Cochrane Library, and Science Direct to review the available medical literature about physical activity after bariatric surgery. The following keywords: sport, physical activity, obesity, bariatric surgery were used to search for papers. Results: This review examines the benefits of PA after bariatric surgery, highlighting its impact on reducing weight regain, maintaining lean body mass, and improving quality of life. It also explores the unique challenges associated with primary obesity and post-bariatric surgery, such as joint pain, loose skin, nutritional deficiencies, and psychological barriers, which often prevent patients from engaging in PA. Conclusions: The review emphasizes the need for clear guidelines, tailored interventions, and multidisciplinary support to address these challenges. By promoting PA and providing comprehensive care, healthcare providers can ensure long-term success and improved quality of life for bariatric patients.